Analysis of Whole-Transcriptome RNA-Seq Data Reveals the Involvement of Alternative Splicing in the Drought Response of Glycyrrhiza uralensis - Li, Guozhi; Xu, Dengxian; Huang, Gang; Bi, Quan; Yang, Mao; Shen, Haitao; Liu, Hailiang (Frontiers in Genetics, 2022)
Alternative splicing (AS) is a post-transcriptional regulatory mechanism that increases protein diversity. There is growing evidence that AS plays an important role in regulating plant stress responses. However, the mechanism by which AS coordinates with transcriptional regulation to regulate the drought response in Glycyrrhiza uralensis remains unclear. In this study, we performed a genome-wide analysis of AS events in G. uralensis at different time points under drought stress using a high-throughput RNA sequencing approach. We detected 2479 and 2764 AS events in the aerial parts (AP) and underground parts (UP), respectively, of drought-stressed G. uralensis. Of these, last exon AS and exon skipping were the main types of AS. Overall, 2653 genes undergoing significant AS regulation were identified from the AP and UP of G. uralensis exposed to drought for 2, 6, 12, and 24 h. Gene Ontology analyses indicated that AS plays an important role in the regulation of nitrogen and protein metabolism in the drought response of G. uralensis. Notably, the spliceosomal pathway and basal transcription factor pathway were significantly enriched with differentially spliced genes under drought stress. Genes related to splicing regulators in the AP and UP of G. uralensis responded to drought stress and underwent AS under drought conditions. In summary, our data suggest that drought-responsive AS directly and indirectly regulates the drought response of G. uralensis. Further in-depth studies on the functions and mechanisms of AS during abiotic stresses will provide new strategies for improving plant stress resistance.